Kualitas Pelayanan Masyarakat di Kecamatan Bontobahari Kabupaten Bulukumba - Andi Risma Jaya (Universitas Muhammadiyah Gorontalo, 2018)
This study aims to determine the quality of community service in Bontobahari District, Bulukumba Regency, South Sulawesi Province. The method used is descriptive method in order to describe the condition of the subject / object of the researcher based on the facts of the field. The primary data source is obtained from structural officials, officers who are directly faced with the application program users. The data collection technique is done through in-depth interviews, observations, questionnaires and documentation. Based on the results of the research, the quality of community service in Bontobahari Subdistrict is quite good, the procedure that must be followed is quite simple, but there are still some community members who find it difficult to prepare the files. The requirements and completion of the incoming file and meeting our immediate requirements are never postponed. The condition of the facilities and infrastructure of services that are clean, neat and orderly so that they can provide comfort to the recipients of the service. The presence of a technology and and information system in human life today can no longer be circumvented and even its presence is a necessity. Penelitian ini bertujuan adalah Untuk mengetahui kualitas pelayanan masyarakat di Kecamatan Bontobahari Kabupaten Bulukumba Provinsi Sulawesi Selatan. Metode yang digunakan metode deskriptif agar dapat mendeskripsikan keadaan subyek/obyek peneliti berdasarkan fakta-fakta lapangan. Sumber data primer didapat dari pejabat struktural. Teknik pengumpulan datanya dilakukan melalui wawancara mendalam, observasi, kuesioner dan dokumentasi.Berdasarkan hasil penelitiaan Kualitas pelayanan masyarakat di Kecamatan Bontobahari sudah cukup baik,Prosedur yang harus dijalani cukup sederhana, namun masih ada beberapa anggota masyarakat merasa kesulitan menyiapkan berkas-berkasnya. Persyaratan dan penyelesaikan berkas yang masuk dan memenuhi persyaratan langsung kami proses tidak pernah menunda-menunda. Kondisi sarana dan prasarana pelayanan yang bersih, rapi dan teratur sehingga dapat memberikan rasa nyaman kepada penerima pelayanan. Kehadiran sistem teknologi dan dan informasi dalam kehidupan manusia saat ini tidak dapat lagi dielakan bahkan kehadirannya sudah merupakan kebutuhan.